Dinamika Pendidikan Islam di Indonesia (Sebuah Tinjauan Historis-Kronologis) - Yovita Dyah Permatasari (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACT In Indonesia, the dynamics of Islamic education have an interesting development. The text below is a chronological search of the phase dynamics. Started from the phase of pre-independence education, the Old Order era, the New Order until the reform era. Each phase has a certain cirikhas and significant influence in the development of Islamic education in Indonesia, both in the field of systems, management, methodology, until the style of Islamic education thought. Keyword: Islamic Education, Education Modernization, Sisdiknas Law.